EXPRESSION AND PURIFICATION OF RECOMBINANT PHENYLALANINE 2,3-AMINOMUTASE FROM PANTOEA AGGLOMERANS - VARGA, Andrea; FILIP, Alina; BENCZE, László Csaba; SÁTORHELYI, Péter; SÁNTA-BELL, Evelin; VÉRTESSY, Beáta G.; POPPE, László; PAIZS, Csaba (Studia Universitatis Babeș-Bolyai Chemia, 2016)
In the present study, the gene of phenylalanine 2,3-aminomutase from Pantoea agglomerans (PaPAM) was cloned into pET-19b vector and used for its expression in competent Escherichia coli cells. The recombinant plasmid, PaPAM-pET-19b, was transformed into competent E. coli strain BL21(DE3)pLysS cells. Overnight culture of the transformed bacteria was induced by the addition of isopropylthio-β-D-galactoside (IPTG) to the final concentrations of 0.1, 0.5 and 1 mM. Also, the effects of different temperatures (18, 25 and 30°C) and the incubation time of PaPAM were examined. The fermentation process was scaled up to 10 L fermentor. Affinity purification conditions were analyzed by SDS-PAGE. The Tm and the activity of the purified enzyme was also investigated.